Beyond the “decarbonised minerals–energy complex”: Rethinking financialisation and state–capital relations in South Africa’s green hydrogen transition - Smith, Robert (New Agenda: SA Journal of Social and Economic Policy, 2025)
This article interrogates South Africa’s green hydrogen ambitions as a key site of the financialisation of development. While hydrogen is increasingly framed through the lens of a ‘decarbonised’ or ‘financialised’ minerals-energy complex (MEC), such readings risk reproducing a power-bloc conception of finance that overstates its expansion while casting the state as a conduit for interests. Drawing on recent critical interventions by Reddy (2025) and Bernards (2025), in combination with initial fieldwork as part of ongoing PhD research, this article argues that these dominant frameworks obscure two central features of the current conjuncture: the persistent financing gap and significant institutional fragmentation within the state itself. Rather than demonstrating the consolidation of a ‘decarbonised MEC’ or the expanding dominance of finance capital, South Africa’s hydrogen landscape reveals the absence of substantial financial participation, alongside a state labouring − often unsuccessfully − to construct conditions of investibility. The article, therefore, calls for rethinking the political economy of hydrogen beyond inherited paradigms and reopening empirical inquiry into how state–capital relations are being actively assembled in the emerging hydrogen economy.